VATIS update : ozone layer protection. Vol. 4, No. 121, Nov-Dec 2013 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2013)
VATIS Update Ozone Layer Protection is published 6 times a year to keep the readers up to date of most of the relevant and latest technological developments and events in the field of Ozone Layer Protection. The Update is tailored to policy-makers, industries and technology transfer intermediaries. Highlights : Global warming 'pause' linked to ozone chemicals ban India advances COOL HABITS initiative in the servicing sector Workshop for the adoption of HCFC alternatives Hybrid heat pump and gas water heater system Super-heated ultrasonic vapor degreaser Halon-free fire extinguisher Foaming technology for PU moldings using carbon dioxide Pesticide alternatives for strawberries THE SCIENCE OF OZONE LAYER . 4 -- Area of Antarctic ozone depletion reaches annual peak -- Global warming ‘pause’ linked to ozone chemicals ban -- Cinderella gas a threat to climate and ozone layer -- Encouraging information about the ozone hole in 2013 -- Acid rain – ozone depletion cause for ancient extinction ODS PHASE-OUT IN INDIA . 6 -- Kochi Metro for green fire fighting -- India advances COOL HABITS initiative in the servicing sector -- Environment friendly water mist fire suppressants IN THE NEWS . 7 -- Twenty fifth meeting of the Parties to the Montreal protocol -- Workshop for the adoption of HCFC alternatives -- Amendments to cut down HCFC by 2015 -- Myanmar moves forward on HCFC emissions -- Sri Lanka to tackle ozone depleting substances -- Indonesia optimistic about slashing HCFC use by 97.5% -- Philippines appeals support to phase-out HCFCs -- Ebara to expand chiller business in Southeast Asia -- HC cooling equipment showcased in Bangkok REFRIGERATION/AIR-CONDITIONING . 10 -- Low GWP refrigerant -- Hybrid heat pump and gas water heater system -- Propane heating and cooling plants in series production -- Compressors using R290 for commercial applications -- High temperature hydrocarbon steam heat pump SOLVENTS . 12 -- New environment friendly cleaning specifications -- Environmentally compatible fluorinated solvents -- ...